1994
DOI: 10.1002/yea.320100805
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoribosylpyrophosphate synthetase (PRS): A new gene family in Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae contains at least four PRS genes, all of which have been cloned and sequenced. Each of the four derived amino acid sequences have more than 60% similarity to the corresponding polypeptides of man, rat, Escherichia coli and Salmonella typhimurium. The PRS1 gene maps on chromosome XI, PRS2 on chromosome V, PRS3 on chromosome VIII and PRS4 on chromosome II. One member of this gene family, PRS1, contains a region of non-homology (NHR) shown by cDNA cloning and sequencing not to be an intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 39 publications
2
48
0
Order By: Relevance
“…The inserts of all the plasmids constructed with PCR-amplified DNA fragments were sequenced. The deduced amino acid sequences of S. cerevisiae PRS1, PRS2, PRS3, and PRS5 were identical to those published previously, whereas the nucleotide sequence of the PRS4 gene used in the present work differed slightly from that published previously (4,5). 2 2 The nucleotide sequence of the PRS4 gene used in the present work differed slightly from that published previously.…”
Section: Methodssupporting
confidence: 70%
“…The inserts of all the plasmids constructed with PCR-amplified DNA fragments were sequenced. The deduced amino acid sequences of S. cerevisiae PRS1, PRS2, PRS3, and PRS5 were identical to those published previously, whereas the nucleotide sequence of the PRS4 gene used in the present work differed slightly from that published previously (4,5). 2 2 The nucleotide sequence of the PRS4 gene used in the present work differed slightly from that published previously.…”
Section: Methodssupporting
confidence: 70%
“…A systematic phenotypic analysis has been carried out with our collection of strains representing all possible combinations of deletions of the five PRS genes. The results obtained define three phenotypes: (i) a synthetic lethal phenotype when PRS1 or PRS3 was deleted from a prs5D strain -simultaneous deletion of PRS2 and PRS4 in combination with loss of PRS1 or PRS3 also results in inviability; (ii) a second phenotype that is encountered in strains containing deletions of PRS1 and PRS3 together or in combination with lack of PRS2 or PRS4 manifests itself as a reduction in growth rate, enzyme activity and nucleotide content; and (iii) deletion of PRS2, PRS4 or PRS5 or combinations thereof has reduced enzyme activity, but are unimpaired in growth and nucleotide profiles (Carter et al, 1994;Hernando et al, 1998Hernando et al, , 1999. Three viable triple deletion combinations, prs2D prs4D prs5D, prs1D prs3D prs4D and prs1D prs2D prs3D, define three minimal subunits, Prs1/Prs3, Prs2/Prs5, Prs4/Prs5, respectively An extensive two-hybrid (Y2H) analysis suggested the existence in the wild-type of two interacting functional entities which may have compensatory function since in the absence of one entity or one of its components the yeast cell can still survive (Hernando et al, 1998(Hernando et al, , 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, the expression pattern of DjPRPS in the head and tail segments was same as that in the intact planarian. (a) (b) (c) [39], and five members are included in PRPS gene family of Saccharomyces cerevisiae [18,20]. All these genes have been cloned and sequenced.…”
Section: The Spatial Expression Pattern Of Djprps In Sexual Intact Anmentioning
confidence: 99%
“…As one of the comparatively conservative genes during evolution, PRPS are found ubiquitously from bacteria to human. It has been reported that PRPS genes have been cloned and sequenced from a variety of organisms, including bacteria [19], yeast [20], protozoa [21], nematodes [22], rat [24] and human [25]. However, except for Hase and co-workers [27], this important gene has not been explored in planarians so far.…”
Section: The Spatial Expression Pattern Of Djprps In Sexual Intact Anmentioning
confidence: 99%
See 1 more Smart Citation